Renewable carbon sources to biochemicals and -fuels: contributions of the smut fungi Ustilaginaceae. (February 2023) - Becker, Johanna; Liebal, Ulf W; Phan, An NT; Ullmann, Lena; Blank, Lars M
Abstract : The global demand for food, fuels, and chemicals increases annually. Using renewable C-sources (i.e. biomass, CO2, and organic waste) is a prerequisite for a future free of fossil carbon. The smut fungi Ustilaginaceae naturally produce a versatile spectrum of valuable products, such as organic acids, polyols, and glycolipids, applicable in the food, energy, chemistry, and pharmaceutical sector. Combined with the use of alternative (co-)substrates (e.g. acetate, butanediol, formate, and glycerol), these microorganisms offer excellent potential for industrial biotechnology, thereby overcoming central challenges humankind faces, including CO2 release and land use. Here, we provide insight into fundamental production capacities, present genetic modifications that improve the biotechnical application, and review recent high-performance engineering of Ustilaginaceae toward relevant platform chemicals. Highlights: Ustilaginaceae are promising production hosts for valuable chemicals. High-performance engineering results in industrially relevant performance metrics. A wide range of substrates can be efficiently converted. Smut fungi can contribute to a sustainable bioeconomy with reduced CO2 emissions.